2022
DOI: 10.1111/jfbc.14064
|View full text |Cite
|
Sign up to set email alerts
|

Insulin mimetic effect of D‐allulose on apolipoprotein A‐I gene

Abstract: Several nutrients modulate the transcriptional activity of the apolipoprotein A-I (apo A-I) gene. To determine the influence of rare sugars on apo A-I expression in hepatic (HepG2) and intestinal derived (Caco-2) cell lines, apo A-I, albumin, and SP1 were quantified with enzyme immunoassay and Western blots while mRNA levels were quantified with real-time polymerase chain reaction. The promoter activity was measured using transient transfection assays with plasmids containing various segments and mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Preclinical studies have suggested that D-allulose and D-tagatose were reported to reduce blood LDL-C or TG level (Kanasaki et al, 2019;Lee et al, 2020;Police et al, 2009b). It was reported in animal or cell experiments that fructose epimer enhanced hepatic lipid metabolism by increasing the production of scavenger receptor class B type 1, proprotein convertase subtilisin/kexin type 9 and apolipoprotein A-I, thereby improving blood lipid homeostasis (Haas et al, 2022;Kanasaki et al, 2020;Kanasaki et al, 2019). However, this antihyperlipidemia effect has not been consistently observed in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have suggested that D-allulose and D-tagatose were reported to reduce blood LDL-C or TG level (Kanasaki et al, 2019;Lee et al, 2020;Police et al, 2009b). It was reported in animal or cell experiments that fructose epimer enhanced hepatic lipid metabolism by increasing the production of scavenger receptor class B type 1, proprotein convertase subtilisin/kexin type 9 and apolipoprotein A-I, thereby improving blood lipid homeostasis (Haas et al, 2022;Kanasaki et al, 2020;Kanasaki et al, 2019). However, this antihyperlipidemia effect has not been consistently observed in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent revelation that highlights the complexity of this seemingly inert sugar is that it upregulates the transcription of the apolipoprotein A1 (ApoA1) gene through its interaction with the transcription factor Sp1 at the insulin response element of the promoter region of the gene. 24 The latter study in cell cultures suggests that D-allulose may have cardioprotective properties by increasing the de novo synthesis of ApoA1. 25 In addition, because glucose transporter genes harbor the insulin response element in their promoter, D-allulose may lower blood glucose levels by upregulating glucose transporters and enhancing tissue glucose uptake; however, it is not known whether ApoA1 gene overexpression can be observed in experimental animals or humans.…”
Section: Rare Sugarsmentioning
confidence: 95%
“…The revelation that d -allulose is a metabolic substrate for Klebsiella pneumoniae is disconcerting because there is the theoretical possibility that the chronic consumption of d -allulose may cause overgrowth of this intestinal pathogen 23 . A recent revelation that highlights the complexity of this seemingly inert sugar is that it upregulates the transcription of the apolipoprotein A1 (ApoA1) gene through its interaction with the transcription factor Sp1 at the insulin response element of the promoter region of the gene 24 . The latter study in cell cultures suggests that d -allulose may have cardioprotective properties by increasing the de novo synthesis of ApoA1 25 .…”
Section: Rare Sugarsmentioning
confidence: 99%
“…Overall, our result supports another evidence that D-allulose plays a beneficial role not only as a chemical sweetener but also gives pharmacological support as an anti-diabetic, probably through its chemical structure as a mimetic sugar bypassing the pancreatic and insulin functions and through its functional structure as an insulin mimetic and modulator of some insulin-responsive genes. 17 Furthermore, D-allulose possesses antiatherogenic property, 17 a metabolic regulator of glucose and lipid metabolism, 18,19 a regulator of postprandial glucose metabolism 20 and is a regulator of muscular glucose disposal. 21 In addition, administration of 25 g of D-allulose did not change blood lipids, uric acid, or hsCR, making D-allulose an excellent, effective, and safe sugar substitute.…”
Section: Role Of D-allulose Treatment On Blood Glucose Levelmentioning
confidence: 99%
“…15 Iida et al further validated the role of acute D-allulose administration in decreasing glycemic responses induced by maltodextrin in normal adults. 16 Conclusively, the potential medicinal role of Dallulose varies from its role as an insulin mimetic and modulator of some insulin-responsive genes, 17 as an anti-atherogenic property, 17 as the metabolic regulator of glucose and lipid metabolism, 18,19 as a regulator of postprandial glucose metabolism 20 and as a regulator of muscular glucose disposal. 21 Considering recent advances, D-allulose may play a beneficial role as a sweetener or sugar substitute as well as a pharmacologic treatment for diabetic conditions.…”
Section: Introductionmentioning
confidence: 99%